Antioxidant study of garlic and red onion: a comparative study - Che Othman, Siti Fairuz; Syed Osman Idid, Syed Zahir Idid; Koya, Mustapha Suleiman; Mohamed Rehan, Aisyah; Kamarudin, Kamarul Rahim (Universiti Putra Malaysia Press, 2011)
Garlic (Allium sativum L.) and red onion (Allium cepa L.) are among the most common ingredients in Malaysian cuisines. These two Allium species are believed to possess medicinal properties including antioxidants. Accordingly, the aim of this study was to compare antioxidant level and activities (i.e. at primary and secondary levels) in both the Allium species collected from markets around Kuantan, Pahang Darul Makmur, Malaysia. Current results of total phenolic content (TPC) assay indicate that TPC is higher in red onion (i.e. 53.43 ± 1.72 mg GAE/100g) as compared to garlic (i.e. 37.60 ± 2.31 mg GAE/100g). In addition, EC50 value of garlic is lower than that of the red onion, showing a higher free radical scavenging activity in garlic than in red onion. However, the primary antioxidant activities of both the samples are lower than the standard antioxidant, BHA. Therefore, there is a poor relationship between the TPCs and the primary antioxidant activities, indicating that the primary antioxidant activities of both the Allium species are not solely due to the phenolic compounds. For secondary antioxidant activity, FIC assay shows that at the highest sample concentration of 1.0 mg/mL, red onion has higher ferrous ion chelating effect (i.e. 45.00 ± 1.73%) as compared to garlic (i.e. 43.29 ± 3.89%). Furthermore, both the Allium samples show slightly higher ion chelating effect than BHA (i.e. 43.14 ± 1.07%) but lower than EDTA (i.e. 97.9 ± 0.07%). Overall, the findings of the present study show a negative relationship between the results of TPC assay, DPPH radical scavenging activity assay, and FIC assay. To strengthen the validity of the present results and to further assess the potential of both the Allium species as natural antioxidant sources, more different assays need to be considered for future work.